Planejamento temático baseado em tarefas no ensino e aprendizagem de inglês a distância - Emidio, Denise Elaine (2017)
The aim of this study is to propose an online English course using a thematic task-based syllabus, on the Moodle plataform. It intends to identify the characteristics of the tasks elaborated and analyze the students’ performances. From the methodological point of view, this is a qualitative-interpretative research, with a virtual ethnographic basis and it was carried out on the Moodle platform, which is offered by a Federal Technology Institution of the interior of São Paulo. The subjects were students of technical and undergraduate courses. The data were collected through semi-structured interview, questionnaire and record of conversations on the platform, Facebook and Skype. Besides these, the tasks elaborated for this study and those that were done by the students were also used. The 40-hour-online English course had a macro-theme called Inventors and Inventions and consisted of three thematic units Top 10 inventors of all time, Nikola Tesla and Leonardo da Vinci. One of the reasons for using task-based thematic syllabus comes from results of researches (BARBIRATO, 1999, 2005; XAVIER, 1999; CASSOLI, 2011; FRANSCESCHINI, 2014) that show the use of tasks can give great opportunities for learners to use the target language. When elaborating the tasks on the Moodle platform, the teacher came across with two main problems: her approach, still with structural influence, and the limitation of some platform tools. The students also encountered some technical and linguistic difficulties in carrying out the tasks. Despite these problems, the empirical results of this research may propose alternatives to foreign language professionals interested in using thematic task-based syllabus in a virtual learning environment.